2020
DOI: 10.9734/ajee/2020/v13i130171
|View full text |Cite
|
Sign up to set email alerts
|

Medical Waste Generation during COVID-19 (SARS-CoV-2) Pandemic and Its Management: An Indian Perspective

Abstract: The generation of biomedical waste has increased many times after the SARS Cov2 commencement. The biomedical waste generated from COVID-19 Patients is very infectious and contaminated. Thus, it is a big challenge with all stakeholders to avoid spreading of COVID-19 through it. This requires monitoring the complete cycle to the grave to be monitored from the cradle, if the spreading needs to be controlled. The COVID-19 waste generation, collection, storage, transportation and disposal is a big challenge withall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 2 publications
0
15
1
1
Order By: Relevance
“…Furthermore, the absence of standard operating procedures and the healthcare waste management committee was an important finding in the hospital. This is in contrary to the national and international (WHO) recommendations of proper waste management during COVID-19 and the experiences of other countries [ 11 , 12 , 18 21 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, the absence of standard operating procedures and the healthcare waste management committee was an important finding in the hospital. This is in contrary to the national and international (WHO) recommendations of proper waste management during COVID-19 and the experiences of other countries [ 11 , 12 , 18 21 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Hazardous MWs are assumed to form 15% of the total waste production in a hospital and that value can also be as high as 35%, depending on the waste production characteristics [ [5] , [6] , [7] ]. According to the literature, production rates of MW in hospitals has increased by up to 280 tons/day during the COVID-19 outbreak [ [8] , [9] , [10] , [11] ]. These wastes require cold and ventilated storage in a separate area from hospitals until transported to incineration facilities by MW municipal trucks, high disposal costs for hospitals, strict emissions control for municipalities, and incineration facilities, and detailed considerations for health risks [ [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…India is producing approximately 550 tons of biomedical waste (BMW) per annum which are treated by only 198 Common Bio-Medical Waste Treatment Facilities (CBMWTFs) and 225 captive incinerators (Singh et al 2019 ; Yadav et al 2020 ). It has been reported that during the present epidemic in Wuhan, China, the city produced 240 tons of additional medical waste per day (Ranjan et al 2020 ; Yu et al 2020 ; Zambrano-Monserrate et al 2020 ).…”
Section: Environmental Perspectives Of Covid-19mentioning
confidence: 99%
“…Dedicated vehicles must be employed to collect COVID-19 ward waste and its sanitization. The proper monitoring is quite essential while disposing of COVID-19 waste so the workers should not get infected by it (Kumar et al 2020 ; Ranjan et al 2020 ; Mahmood et al 2020 ). For discarding the BMW properly, it is important to know the composition so that its proper disposal can be ensured (Ilyas et al 2020 ).…”
Section: Environmental Perspectives Of Covid-19mentioning
confidence: 99%